Knowledge, power and school history in post-independence Malawi: A critical analysis of curriculum change (1964-2022) (Yesterday & Today Journal for History Education in South Africa and abroad, 2022)
Emerging educational research in Africa reveals an eventful course of development for school history curricula in post-colonial African states as they grappled with issues of quality and relevance in history education. In exploring the internationally little-known case of Malawi, the article takes a diachronic approach to retracing the process of history curriculum change from the country’s independence from Britain in 1964 to the time of writing in 2022. The study proposes a systematic analysis of the content, pedagogy and assessment methods foregrounded by evolving history syllabuses in response to curriculum review processes over the last six decades. It also provides insights into the shis undergone by Malawi’s priorities and aspirations in the context of its legacies of European colonialism, one-party dictatorship and authoritarianism and its transition to democracy in the mid1990s. Illuminating the entanglements of these processes with power politics and their contribution to the stagnation of the discipline of history, the article concludes that, although successive reviews have promoted curriculum change over time, they have failed to bring about meaningful reform.
Keywords: Malawi; History Curriculum; Curriculum Reform; Curriculum Politics; Decolonization; Post-colonial; Critical Theory